Exoskeleton gait training to improve lower urinary tract function in people with motor-complete spinal cord injury: A randomized pilot trial - Alison M.M. Williams; Emily Deegan; Matthias Walter; Lynn Stothers; Tania Lam (Medical Journals Sweden, 2021)
Objective: The primary aim of this study was to determine the feasibility of delivering an exoskeleton-assisted walking intervention targeting lower urinary tract function in people with motor-complete spinal cord injury. Secondary aims were to determine if exoskeleton walking activates the pelvic floor muscles, and compare 2 exoskeleton programmes regarding lower urinary tract function. Design: Randomized pilot trial. Subjects: Adults with motor-complete spinal cord injury at or above T10. Methods: Participants were randomized to receive Ekso or Lokomat training. Feasibility outcomes included recruitment rate, adherence, and adverse events. Pelvic floor muscle electromyography was recorded during walking. Urodynamic studies, 3-day bladder diary, and Qualiveen-30 were administered pre- and post-training. Results: Twelve people were screened and 6 people enrolled in the study. Two subjects withdrew from unrelated reasons. There was one adverse event. Pelvic floor muscle activity was greater in the Ekso group. Lower urinary tract function did not clearly change in either group. Conclusion: This pilot study demonstrates the feasibility of delivering an exoskeleton training programme targeting lower urinary tract function. Ekso-walking elicits pelvic floor muscle activity, but it remains unclear how locomotor training impacts lower urinary tract function.